The Curriculum and Learning Systems at Muhammadiyah Boarding School Syamsul Ulum Bandung - Amar Amrullah; Ahmad Firdaus; Lelly Robiatul Adawiyah; Aan Hasanah; Bambang Samsul Arifin (CV. Creative Tugu Pena, 2024)
This article aims to analyze the curriculum and learning system at Muhammadiyah Boarding School Syamsul Ulum Bandung City. The research method used in writing this article is using qualitative method. The results showed that Muhammadiyah Boarding School Syamsul Ulum adopted the 2013 curriculum and the curriculum developed by Dikdasmen Muhammadiyah While the learning system at Muhammadiyah Boarding School Syamsul Ulum applies Active Active Learning and Creative Learning systems that emphasize on the activeness of students in the teaching and learning process. In the teaching and learning process, the material is delivered by the teacher in an interactive, interesting, creative, innovative, and fun way. As a motivation to improve student achievement, various efforts are made. Among other things: improvement and enrichment, moral coaching, integrated counseling involving musyrif, parents, and the community